Sulfur Regulates the Trade-Off Between Growth and Andrographolide Accumulation via Nitrogen Metabolism in Andrographis paniculata - Jian, Shao-Fen; Huang, Xue-Jing; Yang, Xiao-Nan; Zhong, Chu; Miao, Jian-Hua (Frontiers in Plant Science, 2021)
Nitrogen (N) and sulfur (S) are essential mineral nutrients for plant growth and metabolism. Here, we investigated their interaction in plant growth and andrographolide accumulation in medicinal plant Andrographis paniculata grown at different N (4 and 8 mmol·L−1) and S concentration levels (0.1 and 2.4 mmol L−1). We found that increasing the S application rate enhanced the accumulation of andrographolide compounds (AGCs) in A. paniculata. Simultaneously, salicylic acid (SA) and gibberellic acid 4 (GA4) concentrations were increased but trehalose/trehalose 6-phosphate (Tre/Tre6P) concentrations were decreased by high S, suggesting that they were involved in the S-mediated accumulation of AGCs. However, S affected plant growth differentially at different N levels. Metabolite analysis revealed that high S induced increases in the tricarboxylic acid (TCA) cycle and photorespiration under low N conditions, which promoted N assimilation and S metabolism, and simultaneously increased carbohydrate consumption and inhibited plant growth. In contrast, high S reduced N and S concentrations in plants and promoted plant growth under high N conditions. Taken together, the results indicated that increasing the S application rate is an effective strategy to improve AGC accumulation in A. paniculata. Nevertheless, the interaction of N and S affected the trade-off between plant growth and AGC accumulation, in which N metabolism plays a key role.